2022
DOI: 10.21037/jtd-22-606
|View full text |Cite
|
Sign up to set email alerts
|

Qishen Yiqi dropping pills improve isoproterenol-induced cardiomyocyte hypertrophy by regulating X-inactive specific transcript (XIST) expression in rats

Abstract: Background: This study aimed to explore the potential mechanism of Qishen Yiqi dropping pills (QYDPs) in the treatment of chronic heart failure (CHF) by regulating the expression of lncRNAs during CHF.Methods: Differences in the expression of the long non-coding RNA (lncRNA), X-inactive specific transcript (XIST), in an isoproterenol (ISO)-induced cardiomyocyte hypertrophy model treated with QYDPs was analyzed by reverse transcription quantitative polymerase chain reaction (RT-qPCR). A cell counting kit-8 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Over the past decades, several in vivo studies have attempted to elucidate the mechanism of action of QSYQ in the treatment of heart failure ( 45 ). In a mouse model of high-fat diet-induced heart failure with preserved ejection fraction (HFpEF), it was observed that QSYQ significantly improved cardiac function and myocardial remodeling in mice, possibly through the inhibition of microvascular endothelial inflammation and activation of the NO-cGMP-PKG pathway ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, several in vivo studies have attempted to elucidate the mechanism of action of QSYQ in the treatment of heart failure ( 45 ). In a mouse model of high-fat diet-induced heart failure with preserved ejection fraction (HFpEF), it was observed that QSYQ significantly improved cardiac function and myocardial remodeling in mice, possibly through the inhibition of microvascular endothelial inflammation and activation of the NO-cGMP-PKG pathway ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Once the cells reached 60–80% confluence, a small interfering (si) lncRNA TINCR (si-TINCR) or lncRNA TINCR overexpression plasmid (ov-TINCR) (each 100 nM), miR-193b-3p mimic or inhibitor (each 50 nM), and their negative controls (NCs) were transfected into H9C2 cardiomyocytes by treatment with Lipofectamine ® 2000 (Invitrogen, Thermo Fisher Scientific, Inc.) for 4 hours. The H9C2 cells were pretreated with different concentrations of QYDP (0, 10, 50, 100, 250, and 500 µg/mL) as described in our previous study ( 25 ), and then stimulated with Ang II (0.1 M; Millipore, Billerica, MA, USA) for 24 hours, as described in a previous study ( 26 ). GenePharma Biotechnology Co., Ltd., (Shanghai, China) synthesized the lncRNA TINCR and miR-193b-3p mimic/inhibitor.…”
Section: Methodsmentioning
confidence: 99%